Three men posing together - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows three men posing together. They are all turned to the left, each with their backs to the man behind them. They all appear to be in dress clothes. The man to the far left is in a tuxedo. The man on the far right appears to be an African American and has his left hand resting on the middle man's upper arm.